Energy trade and cooperation between the EU and CIS countries - Vladimer Papava; Sabit Bagirov; Leonid Grigoriev; Wojciech Paczynski; Marcel Salikhov (Center for Social and Economic Research (CASE), 2009)
The report reviews key issues in energy trade and cooperation between the EU and CIS countries. It describes historical trends of oil and gas demand in the EU, other European and CIS countries and offers demand forecasts until 2030. Recent developments in oil and gas production and exports from Russia and Caspian countries are covered in detail leading to the discussion of the likely export potential of these regions. The key factors determining the production outlook, trade-offs and competition related to energy resources transportation choices are also discussed. The report also covers the interests and role of transit countries in relations between producer and consumer regions. The analytical section leads to policy recommendations that focus mainly on the EU.
Keywords: Q41; Q48; Q43; 330; energy supply; energy demand; gas and oil resources; Caspian countries; EU; Russia; Caucasus; Internationale Wirtschaftsbeziehungen; Energiereserven; Energieversorgung; Erdölkonsum; Erdgas; EU-Staaten; Russland; GUS-Staaten